The Effect of Maximal Aerobic Exercises on Some Biomechanical Variables of Soccer Players - Khadem, Yousif; Ahmed, Ali (Journal of Physical Education, 2022)
The research aimed at identifying the effect of maximal aerobic abilities on some biochemical indicators and mTOR protein responsible for muscular hypertrophy in muscular fiber of soccer players. It also aimed at identifying the benefits of maximal aerobic training on the physical fitness development in general and supporting biochemical indicators in specific. In addition to that, it aimed at identifying the effect of mTOR protein on athlete’s muscular fibers. The researchers used the experimental method on (10) Al Etesalat sport club players participating in the send class league. the researchers used polar belts, GPS vest to control training intensity. The results showed significant differences in biochemical variables (CPK enzyme and lactic acid). The level of mTOR protein did not develop on the contrary it decreased. The researchers concluded that aerobic abilities training increased anaerobic indicators and developed them as well while decreasing mTOR protein responsible for muscular hypertrophy. The researchers recommended making similar studies on the effect of maximal aerobic abilities on other biochemical indicators as well as the necessity of making studies on mTOR protein’s relationship with other components like Insulin, lactic, and AMPK.